TRINIBACULUM ALTIPARANAE SP. N., A NEW DACTYLOGYRID SPECIES (MONOGENEA) OF THE ASTYANAX ALTIPARANAE (OSTEICHTHYES: CHARACIDAE) IN THE PEIXE RIVER, SOUTHEASTERN BRAZIL - Doro Abdallah, Vanessa (2013)
This article describes a new species –Trinibaculum altiparanae sp. n. –found in the gills of the Astyanax altiparanae Garutti & Britski, 2000. Fish were collected from the Peixe River in the municipality of Anhembi, State of São Paulo, Brazil, in March 2010. This paper describes the third species of the genus Trinibaculum. This new species is characterized by having an accessory structure that does not articulate with the male copulatory organ (MCO). This accessory structure has a basally bifid, well-curved distal end, tapered with a terminal flabellate piece. The male copulatory organ is a simple tube with less than one ring coiled counterclockwise; two similar curved dorsal bars; a ventral bar with concave ends and a posterior projection, a dorsal anchor with a truncated deep root and a slightly curved shaft, a ventral anchor with a curved shaft and differently shaped and sized hooks. Those features distinguish the new species from the two other species previously described in this genus: Trinibaculum braziliensis Kritsky, Thatcher & Kayton, 1980 was found parasitizing Brycon melanopterus (Cope, 1872) and Trinibaculum rotundus Karling, Lopes, Takemoto & Pavanelli, 2011 was found parasitizing Schizodon borellii (Boulenger, 1900).